Evaluasi Kebijakan Berbasis Responsivitas Terhadap Rencana Kontinjensi Tsunami Provinsi Sumatera Barat - Ory Riandini; Roni Ekha Putera; Hendri Koeswara (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
West Sumatra Province has a high risk of tsunami disaster. From this situation description, an appropriate and relevant Contingency Plan is needed so that it can be used effectively when a disaster occurs. This research explains the evaluation of West Sumatra Province's tsunami contingency planning policy based on the descriptor of public policy responsiveness proposed by William Dunn. The approach used in this research is descriptive qualitative with purposive sampling to determine informants. Meanwhile, the data analysis technique uses the triangulation method. The results of the research show that from the descriptor of the responsiveness of West Sumatra's tsunami contingency plan policy, there is doubt about its readiness to face this disaster. This is because the necessary measures have not gone through a review process to adapt them to the threats and required resource requirements. From the research findings, it can be explained that the responsiveness descriptor, namely focusing on crucial issues and intensity of preferences, has not been implemented in the West Sumatra tsunami contingency plan policy.